The order of Tishreen University Faculties in term of student’s satisfaction with faculty members and its relation with some variables - shrif, Leila; Hatem, Fahd (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This research aimed to determine the order of Tishreen University colleges in term of satisfaction with the faculty members, and to determine whether that satisfaction affected by variables: (gender, University Specialization, and the collage year), using the "satisfaction with the faculty members " scale. A total of (749) undergraduate from Tishreen University students in all faculties, participated in this research. Search results are summarized as follows: faculties of economics and physical education and dentistry have got at the highest averages in the ranking of colleges by satisfaction with the teaching staff, while the faculties of Architecture and Literature and Sciences have got at the lower averages. and there were a differences among the members of the research sample in the scale according to the gender variable in favor of females, and there were a differences according to the collage year variable, and there were no differences according to University Specialization variable.